1998
DOI: 10.1002/(sici)1096-8628(19980901)79:2<121::aid-ajmg8>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 16 and trisomy 16 mosaicism: A review

Abstract: A review of all prenatal and postnatal diagnoses of trisomy 16 and trisomy 16 mosaicism was carried out in the context of the current understanding of confined placental mosaicism and uniparental disomy (UPD). The prenatal detection of trisomy 16 cells is associated with a high probability of fetal death, preterm delivery, intrauterine growth retardation, and fetal anomalies. Birth defects were typical of those seen in nonmosaic partial duplications of chromosome 16. Surprisingly, anomalies were sometimes limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(68 citation statements)
references
References 82 publications
1
65
2
Order By: Relevance
“…All five pregnancies were complicated by fetal growth retardation. Other studies have also shown extremely high levels of hCG (2,22). Our patient, however, displayed an hCG level within the normal range on first trimester screening; the AFP level was also within the normal range (26 IU/mL, measured at 16 weeks in amniotic fluid; normal range, 15-30 IU/mL).…”
Section: Papp-acontrasting
confidence: 47%
See 1 more Smart Citation
“…All five pregnancies were complicated by fetal growth retardation. Other studies have also shown extremely high levels of hCG (2,22). Our patient, however, displayed an hCG level within the normal range on first trimester screening; the AFP level was also within the normal range (26 IU/mL, measured at 16 weeks in amniotic fluid; normal range, 15-30 IU/mL).…”
Section: Papp-acontrasting
confidence: 47%
“…In trisomy 16, an early embryonic arrest usually results in a miscarriage between 8 and 15 weeks of gestational age. Trisomy 16 miscarriages show empty sacs, disorganized embryos, or minimal embryonic development (2). Almost all cases of trisomy 16 surviving in the second trimester of pregnancy are found to be mosaic (meaning that the cell lines contain both euploid and trisomic cells) (5).…”
mentioning
confidence: 99%
“…By our approach it was not possible to detect low level trisomy in the placenta or in the foetus, taking into consideration that trisomic cells, may be confined to only one tissue compartment. 17 A phenotypic effect of maternal UPD(9) seems to be unlikely since there is no evidence for an imprinting locus on maternal chromosome 9 (Table 3). Therefore, maternal UPD(9) appears to be without major clinical consequences unless a recessive mutation is reduced to homozygosity, 18,19 whereas trisomy 9 mosaicism results in severe congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 16 is the most common autosomal trisomy of spontaneous abortions during the first trimester, and approximately 1% of clinically diagnosed conceptions are predicted to exhibit trisomy 16 [1]. Among trisomy 16 diagnoses, confined placental mosaicism (CPM) of trisomy 16 is defined as pregnancies wherein trisomy 16 cells are exclusively localized to the placenta.…”
Section: Introductionmentioning
confidence: 99%